Determination of Placental Blood Flow by External Monitoring of 113mIn - Olkkonen, H.; Suonio, S.; Haring, P. (Nuklearmedizin - NuclearMedicine, 1976)
A simple and noninvasive technique was developed to evaluate the blood perfusion rate within human placenta. The method is based on monitoring the accumulation of the isotope 113mIn in the placental intervillous space using a single detector as a measuring device. The result was expressed as an accumulation index calculated from the tracer appearance curve. The In accumulation index was significantly lower in preeclamptic patients than in the controls, but with a marked overlapping. The In index was significantly correlated with the simultaneously recorded maternal minute volume, 24-hour estrogen excretion and birthweight. No correlation was found with the placental weight or Laakso’s perfusion index. Uterine contractions induced a significant decrease in the In index. The authors conclude that the In accumulation index can be used as an objective measure of the placental blood flow.